Cytokinin Regulation of Source-Sink Relationships in Plant-Pathogen Interactions - McIntyre, Kathryn E.; Bush, Daniel R.; Argueso, Cristiana T. (Frontiers in Plant Science, 2021)
Cytokinins are plant hormones known for their role in mediating plant growth. First discovered for their ability to promote cell division, this class of hormones is now associated with many other cellular and physiological functions. One of these functions is the regulation of source-sink relationships, a tightly controlled process that is essential for proper plant growth and development. As discovered more recently, cytokinins are also important for the interaction of plants with pathogens, beneficial microbes and insects. Here, we review the importance of cytokinins in source-sink relationships in plants, with relation to both carbohydrates and amino acids, and highlight a possible function for this regulation in the context of plant biotic interactions.